Biomaterials in Cardiovascular Research: Applications and Clinical Implications. (7th May 2014) - Jaganathan, Saravana Kumar; Supriyanto, Eko; Murugesan, Selvakumar; Balaji, Arunpandian; Asokan, Manjeesh Kumar
Abstract : Cardiovascular biomaterials (CB) dominate the category of biomaterials based on the demand and investments in this field. This review article classifies the CB into three major classes, namely, metals, polymers, and biological materials and collates the information about the CB. Blood compatibility is one of the major criteria which limit the use of biomaterials for cardiovascular application. Several key players are associated with blood compatibility and they are discussed in this paper. To enhance the compatibility of the CB, several surface modification strategies were in use currently. Some recent applications of surface modification technology on the materials for cardiovascular devices were also discussed for better understanding. Finally, the current trend of the CB, endothelization of the cardiac implants and utilization of induced human pluripotent stem cells (ihPSCs), is also presented in this review. The field of CB is growing constantly and many new investigators and researchers are developing interest in this domain. This review will serve as a one stop arrangement to quickly grasp the basic research in the field of CB.